Analisis Campuran Serat Serabut Kelapa Dengan Serat Daun Nanas Sebagai Bahan Penambah Serat Sellulosa Pada Split Mastic Asphalt (SMA) - R Efrida; M H Gultom; I Dewi; D R W Oktaviani (Cered Indonesia Institute, 2020)
Split Mastic Asphalt (SMA) is a thin surface layer, has good resistance to grooves (rutting) and has a high durability so that the SMA is suitable for heavy surface road surfaces. The main constituent material is aggregate and asphalt, this study tried to use coconut fiber fibers with pineapple leaf fiber as added material. This study aims to determine how much the value of Marshall characteristics in asphalt mixes using coconut fiber fibers with pineapple leaf fibers as added ingredients. The results showed that the use of coconut fiber fibers with pineapple leaf fibers will affect the characteristics of the asphalt mixture. The Marshall Test data obtained obtained the highest value of stability of 874 kg, bulk density of 2.231 gr / cc, flow of 2.51 mm, void in mineral aggregate of 45.42%, Air Voids 4.89% So it can be concluded that the content pineapple leaf fiber meets Marshall Test Requirements